1982
DOI: 10.1139/v82-151
|View full text |Cite
|
Sign up to set email alerts
|

The design and synthesis of nonpeptide compounds as mimics of a conformation of methionine-enkephaline

Abstract: A model for the active conformation of methionine-enkephalin containing a P-turn was derived from computer modeling. Using a trans-perhydronaphthalene as a structural template and a mimic of the p-turn, target compounds were designed and synthesized. Thus, a key intermediate, trans-3-oxo-5~-formamidomethyl-8a-phenylmethylperhydronaphthalene, was prepared by two different routes from cyclohexanone.The addition of a methionine-like side-chain to this key intermediate was best achieved by a reaction with the anio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…Purified sTva47 required oxidative folding to form the correct disulfide bonds. As was found for oxidation of LBr from the LDLR family of receptors [12,17,18,20], calcium was required to selectively form a single disulfide bonding pattern, which we assumed matched that of the native Tva and the LDLR LBr as previously suggested [9] (Wang et al have reported similar findings [23]). After suitable conditions were defined, oxidation was carried out using purified MBP–sTva47 in order to use correctly oxidized sTva47 attached to MBP for surface plasmon resonance binding experiments (see below).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Purified sTva47 required oxidative folding to form the correct disulfide bonds. As was found for oxidation of LBr from the LDLR family of receptors [12,17,18,20], calcium was required to selectively form a single disulfide bonding pattern, which we assumed matched that of the native Tva and the LDLR LBr as previously suggested [9] (Wang et al have reported similar findings [23]). After suitable conditions were defined, oxidation was carried out using purified MBP–sTva47 in order to use correctly oxidized sTva47 attached to MBP for surface plasmon resonance binding experiments (see below).…”
Section: Resultssupporting
confidence: 76%
“…NOE cross‐peak connectivities and preliminary structural calculations suggested a unique disulfide bonding pattern in agreement with the topology suggested by mutagenic studies [9] and comparison to other LDLR LBrs. Hence, the three disulfide bonds were defined for further structural calculations with DYANA and AMBER.…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…2B, lanes 2-14). Although there is some variation in the receptor levels of the mutants, all are expressed well above the minimum level required for full viral receptor function by wt Tva (21). The numerous bands observed for wt Tva, TL4, and the TL4 mutants are most likely a result of modification by N-and O-glycosylation, which has been observed previously with wt Tva (H. Wang, D. Chu, K.G., H. E. Varmus, and P.B., unpublished data).…”
Section: Ldl-a4 Cannot Replace the Ldl-a Module Of Tva For Viralmentioning
confidence: 99%